2005
DOI: 10.5194/angeo-23-2011-2005
|View full text |Cite
|
Sign up to set email alerts
|

Seven year satellite observations of the mean structures and variabilities in the regional aerosol distribution over the oceanic areas around the Indian subcontinent

Abstract: Abstract. Aerosol distribution over the oceanic regions around the Indian subcontinent and its seasonal and interannual variabilities are studied using the aerosol optical depth (AOD) derived from NOAA-14 and NOAA-16 AVHRR data for the period

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
43
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 32 publications
4
43
0
Order By: Relevance
“…The strong contribution from nss-SO 2− 4 was in agreement with previous findings where virtually all nss-SO 2− 4 was likely to have been derived from the marine biogenic source of dimethyl sulfide (Norman et al, 2003). The strong contribution from NaCl, as expected in marine influenced air, was also in agreement with Norman et al (2003).…”
Section: Data Selectionsupporting
confidence: 90%
See 3 more Smart Citations
“…The strong contribution from nss-SO 2− 4 was in agreement with previous findings where virtually all nss-SO 2− 4 was likely to have been derived from the marine biogenic source of dimethyl sulfide (Norman et al, 2003). The strong contribution from NaCl, as expected in marine influenced air, was also in agreement with Norman et al (2003).…”
Section: Data Selectionsupporting
confidence: 90%
“…is mainly a contributor of biogenic derived sulfur containing particles and sea salts (Norman et al, 2003). Considering both the source regions and the meteorological situation leads to the election of two time periods being representative for continental influenced air with relatively high light absorption of BC (4 Mm −1 ) and for air with a minimal influence from combustion sources (0.4 Mm −1 ).…”
Section: Data Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…This long range transport can modify aerosol properties such as their concentration, size distribution and chemical composition (Jennings and O'Dowd, 1990;Krishnamurti et al, 1998;Moorthy et al, 2005). Observations during the INDOEX (Indian Ocean Experiment, 1998) and the ARMEX-I (in 2001) have shown that the atmosphere over the Arabian Sea is strongly influenced by aerosols from west Asia, Africa and east/south east Asia brought by winds (Moorthy and Saha, 2000;Li and Ramnathan, 2002;Vinoj and Satheesh, 2003;Suresh Babu et al, 2004;Nair et al, 2005).…”
Section: Introductionmentioning
confidence: 99%